Transiting of Excel Worksheet to Online System for Calista Music Centre - Lim, Hui Wen; Darman, Rozanawati (Applied Information Technology And Computer Science, 2023)
The implementation of the Music Centre Management System for Calista Music Centre has the goal to design, develop and test the web-based music centre management system of the music centre that uses a structured approach to provide individualized functions for each kind of user. The implemented system utilizes an Agile development methodology. There are three kinds of users in the system which are the administrator, instructor and student. Also, the implemented system provides six functional modules such as login, inventory management, scheduling management, attendance management, payment management and profile management. The implemented system carried out the test plan to ensure the modules functioned as planned. In short, the implemented system improves the management performance of Calista Music Centre and provides a platform to fulfil the requirement of users.